2022
DOI: 10.5944/ried.25.2.32332
|View full text |Cite
|
Sign up to set email alerts
|

La Inteligencia Artificial como recurso educativo durante la formación inicial del profesorado

Abstract: La Inteligencia Artificial (IA) se presenta como una tecnología emergente que facilita la personalización del aprendizaje y prepara a la juventud para un cambiante mercado laboral marcado por nuevos requerimientos sociales. Este trabajo describe cómo se diseñó y desarrolló una formación virtual destinada a ampliar el conocimiento sobre la IA de 76 profesores en formación inicial que cursaban la asignatura TIC aplicadas a la Educación del Grado de Infantil de la Universidad de Extremadura. A través de un enfoqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Figure 3 shows that most of the publications retrieved are in English. In the case of AI, we found that 66 papers were in English (e.g., [47,48]), whereas only three were in Spanish [49][50][51]. Moreover, we retrieved 35 papers in English applying XR in higher education (e.g., [52,53]).…”
Section: Languagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows that most of the publications retrieved are in English. In the case of AI, we found that 66 papers were in English (e.g., [47,48]), whereas only three were in Spanish [49][50][51]. Moreover, we retrieved 35 papers in English applying XR in higher education (e.g., [52,53]).…”
Section: Languagesmentioning
confidence: 99%
“…Whilst the second investigated the quality of education and the image of a university using remote education and AI based on faculty and staff assessments [85]. Following this trend, [51] developed a virtual course for enhancing knowledge of AI tools and their application to future educators.…”
Section: Best Practicesmentioning
confidence: 99%
“…(Fu Lee, 2023). In line with these points (Ayuso & Gutiérrez, 2022) indicates that Artificial Intelligence (AI) is presented as an emerging technology that facilitates the personalization of learning and prepares young people for a changing labor market marked by new social requirements. Having made the above considerations, the general objective of this research is focused on analyzing the preferences towards Artificial Intelligence (AI) in university professors in Ecuador, particularly those who teach the course of Microeconomics.…”
Section: Introductionmentioning
confidence: 99%
“…En esta línea, Rodríguez-García et al (2021) proponen el uso de la herramienta Learning ML tras desarrollar una experiencia de aprendizaje virtual durante la pandemia con alumnado de entre 10 y 16 años. De la experiencia se desprende la constatación de un aumento de la comprensión del alumnado sobre los fundamentos del Machine Learning y que el alumnado afirmaba haber encontrado la herramienta útil, atractiva y fácil de usar (del Puerto & Esteban, 2022).…”
Section: Introductionunclassified